Holistic Requirements for Interdisciplinary Development Processes - Lankeit, Christopher; Michael, Jan; Henke, Christian; Trächtler, Ansgar (Proceedings 1st International Workshop on Learning from other Disciplines for Requirements Engineering)

Model-based precision position and force control of SMA actuators with a clamping application - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (Mechatronics)

Rapid-Control-Prototyping as part of Model-Based Development of Heat Pump Dryers - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Bockholt, Marcos; Möhlenkamp, Andreas; Katter, Michael (Procedia Manufacturing)

Systemmodelle als Schlüssel zu durchgängigen XIL-Testszenarien - Schmitz, Joachim; Fockel, Markus (Tag des Systems Engineering 2017)
Intelligente technische Systeme, wie autonom fahrende Fahrzeuge, werden in einem hohen Maß durch Software realisiert. Der Weg zum autonomen Fahren führt unweigerlich über eine steigende Vernetzung von Steuergeräten im Fahrzeug und über Fahrzeuggrenzen hinweg. Damit einher geht eine stetig steigende Komplexität der Software. Deshalb liegt es auf der Hand, dass die systematische Qualitätssicherung für derartige technische Systeme sehr früh, also bereits entwicklungsbegleitend, erfolgen muss. Dazu lässt sich das Software-in-the-Loop-Verfahren einsetzen, das auf etablierte Techniken des Hardware-in-the-Loop-Verfahrens zurückgreift. Eine besondere Herausforderung besteht darin, Simulationsmodelle und Testbibliotheken sowie die zugehörigen Visualisierungs- und Testwerkzeuge in beiden Welten synergetisch zu nutzen. Das Ziel ist eine einheitliche X-in-the-Loop (XIL) Basis für beide Verfahren. Der Schlüssel zu einer einheitlichen Basis für durchgängige XIL-Testszenarien ist der Einsatz eines übergeordneten Systemmodells. Es definiert die Systemgrenze und umliegenden Systeme in der Umwelt. Zudem dient das Systemmodell als Ordnungsschema für die Ablage der Artefakte wie Verhaltensmodelle, Testskripte, Parametersätze oder Workflows. Ein zentrales Datenmanagementwerkzeug, welches sämtliche Strukturinformationen, Verhaltensmodelle und Variantenbezüge verknüpft, ermöglicht ein teilautomatisches Umschalten zwischen den Testszenarien. In diesem Beitrag stellen wir eine solche Lösung vor.

How to Efficiently Build a Front-End Tool for UPPAAL: A Model-Driven Approach - Schivo, Stefano; Yildiz., Bugra M.; Ruijters, Enno; Gerking, Christopher; Kumar, Rajesh; Dziwok, Stefan; Rensink, Arend; Stoelinga, Mariëlle (Dependable Software Engineering, 3rd International Symposium (SETTA 2017))

Model-based Requirement Pattern Catalog - Fockel, Markus; Holtmann, Jörg; Koch, Thorsten; Schmelter, David
Scenario-based requirements engineering addresses the message-based coordination of software-intensive systems and enables, if underpinned with formal languages, automatic requirements validation techniques for improving the quality of a requirements specification. One of such requirements engineering approaches bases on a recent visual Live Sequence Chart variant compliant to the Unified Modeling Language, so-called Modal Sequence Diagrams (MSDs). The usage of patterns is known to be constructive thanks to assembling solutions by means of reusable building blocks that are proven in practice, so that recurring problems do not need to be solved over and over again. Thus, patterns also gained momentum in the area of requirements documentation. In this technical report, we introduce a model- and scenario-based pattern catalog for MSD requirements. Our MSD requirement pattern catalog consolidates and unifies 86 requirement patterns from three well-known, practice-oriented requirement pattern catalogs, each covering different aspects.

Specification and Verification for Real-Time Coordination Protocols of Cyber-physical Systems - Dziwok, Stefan
Cyber-physische Systeme (CPSs) sind die nächste Generation von eingebetteten Systemen, die fortwährend ihre Zusammenarbeit koordinieren, um anspruchsvolle Funktionen zu erfüllen. Die Koordination zwischen ihnen kann in Software mittels asynchroner Nachrichtenkommunikation realisiert werden. Um die funktionale Korrektheit der Software zu gewährleisten, ist aufgrund der Kritikalität dieser Systeme eine formale Verifikation wie z.B. Model Checking notwendig. Die Eingabesprache eines Model Checkers unterstützt jedoch domänenspezifische Aspekte wie asynchrone Kommunikation nicht direkt, wodurch diese vom Softwareingenieur mittels zahlreicher Modellelemente spezifiziert werden müssen. Dies ist hochgradig komplex und somit fehleranfällig. Im Rahmen dieser Arbeit wird eine modellgetriebene Methode zur domänenspezifischen Spezifikation und vollautomatischen Verifikation der nachrichtenbasierten Koordination von CPSs präsentiert. Mit Hilfe dieser Methode kann der Softwareingenieur die Koordination kompakt modellieren und muss nicht länger verstehen, wie seine Spezifikation auf der Ebene des Model Checkers ausgedrückt wird. Insgesamt wird die Komplexität für den Softwareingenieur somit deutlich handhabbarer. Bezüglich der Spezifikation einer solchen Koordination definiert die Arbeit eine domänenspezifische Sprache namens Real-Time Coordination Protocols (RTCPs). Darüber hinaus wird eine domänenspezifische Sprache zur Spezifikation von Verifikationseigenschaften eingeführt und Entwurfsmuster für RTCPs präsentiert, um die Anzahl der Modellierungsfehler zu senken.

Toward Learning Realizable Scenario-based, Formal Requirements Specifications - Schmelter, David; Greenyer, Joel; Holtmann, Jörg (4th International Workshop on Artificial Intelligence for Requirements Engineering (AIRE))
Distributed, software-intensive systems such as fully automated cars have to handle various situations employing message-based coordination. The growing complexity of such systems results in an increasing difficulty to achieve a high quality of the systems’ requirements specifications, particularly w.r.t. the realizability of the specifications. Scenario-based requirements engineering addresses the message-based coordination of such systems and enables, if underpinned with formal languages, automatic requirements validation techniques for proving the realizability of a requirements specification. However, formal requirements modeling languages require a deep knowledge of requirements engineers and typically require many manual iterations until they find a realizable specification. In order to support requirements engineers in the stepwise development of scenario-based requirements specifications, we propose to evolve a high-quality specification from a (presumably unrealizable) manually created specification employing an evolutionary algorithm. In this paper, we show our results on automatically evolving new assumptions on the systems’ environment behavior that guarantee a realizable requirements specification. Based on this contribution, we outline our research roadmap toward our long-term goal of automatically supporting requirements engineers in finding high-quality requirements specifications.

Improving the Product Control of Mechatronic Systems Using Key Performance Indicators - Wohlers, Benedict; Dziwok, Stefan; Bremer, Christian; Schmelter, David; Lorenz, Wadim (Proceedings of the 24th International Conference on Production Research (ICPR))

Reducing the Verbosity of Imperative Model Refinements by using General-Purpose Language Facilities - Gerking, Christopher; Schubert, David; Budde, Ingo (Theory and Practice of Model Transformation, 10th International Conference (ICMT 2017))

Verteilte statische Analyse zur Identifikation von kritischen Datenflüssen für vernetzte Automatisierungs- und Produktionssysteme - Ghassemi, Faezeh; Meyer, Matthias; Pohlmann, Uwe; Priesterjahn, Claudia
Moderne und Automatisierungs- und Produktionssysteme speichern viele schützenswerte Daten wie zum Beispiel Produktionsmengen oder Verfahrenseinstellungen. Sie werden von speicherprogrammierbaren Steuerungen (SPS) gesteuert. Eine SPS bietet eine Vielzahl von Netzwerk-/Datenschnittstellen. Insbesondere Schnittstellen zum Internet ermöglichen neue Funktionalitäten, sind aber auch mögliche Angriffspunkte. Neben einer Netzwerktrennung durch Firewalls sollte zusätzlich programmatisch unterbunden werden, dass auf kritische/sensible Daten direkt oder indirekt über einen kritischen, unerwünschten Datenfluss zugegriffen werden kann. Bereits während der Entwicklung einer Anlage kann der Steuerungscode mittels statischer Programmanalyse untersucht werden. Die unabhängige Analyse von einzelnen Programmen reicht aber bei vernetzten Anlagen nicht aus, da sich der kritische Datenfluss erst aus der Kombination von Programm- und Netzwerkverhalten ergeben kann. Deshalb stellen wir in diesem Beitrag erste Ideen für eine verteilte statische Analyse der Steuerungssoftware einer vernetzten Industrieanlage vor, welche es ermöglicht den Datenfluss der gesamten vernetzten Anlage zu betrachten. Hierdurch wird es möglich zu beurteilen, ob kritische/sensible Daten die vernetzte Anlage verlassen oder ob diese manipuliert werden können.

Formal Definition and Proofs for the MechatronicUML Allocation Specification Language - Hüwe, Marcus; Pohlmann, Uwe

Flexible Specification of STEP Application Protocol Extensions and Automatic Derivation of Tool Capabilities - Koch, Thorsten; Holtmann, Jörg; Lindemann, Timo (Proceedings of the 5th International Conference on Model-Driven Engineering and Software Development)
Original equipment manufacturers (OEMs) build mechatronic systems using components from several suppliers in industry sectors like automation. The suppliers provide geometrical information via the standardized exchange format STEP, such that the OEM is able to virtually layout the overall system. Beyond the geometrical information, the OEM needs additional technical information for his development tasks. For that reason, STEP provides an extension mechanism for extending and tailoring STEP to project-specific needs. However, extending STEP moreover requires extending several capabilities of all involved tools, causing high development effort. This effort prevents the project-specific utilization of the STEP extension mechanism and forces the organizations to use awkward workarounds. In order to cope with this problem, we present a model-driven approach enabling the flexible specification of STEP extensions and particularly the automatic derivation of the required further capabilities for two involved tools. We illustrate and evaluate the approach with an automation production system example.

Integrated and Iterative Systems Engineering and Software Requirements Engineering for Technical Systems (Précis) - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the Software Engineering 2017)
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of a discipline-spanning system model. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, for example, into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic and iterative transition from MBSE to model-based software requirements engineering, which we present in this talk. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Model-Driven Allocation Engineering – Abridged Version - Pohlmann, Uwe; Hüwe, Marcus (GI-Edition, Lecture Notes in Informatics, Software Engineering 2017, Proceedings)

Towards an Automated Synthesis of a Real-time Scheduling for Cyber-physical Multi-core Systems - Geismann, Johannes; Pohlmann, Uwe; Schmelter, David (Proceedings of the 5th International Conference on Model-Driven Engineering and Software Development)
Modern Cyber-physical Systems are executed in physical environments and distributed over several Electronic Control Units using multiple cores for execution. These systems perform safety-critical tasks and, therefore, have to fulfill hard real-time requirements. To face these requirements systematically, system engineers de- velop these systems model-driven and prove the fulfillment of these requirements via model checking. It is important to ensure that the runtime scheduling does not violate the verified requirements by neglecting the model checking assumptions. Currently, there is a gap in the process for model-driven approaches to derive a feasible runtime scheduling that respects these assumptions. In this paper, we present an approach for a semi- automatic synthesis of behavioral models into a deterministic scheduling that respects real-time requirements at runtime. We evaluate our approach using an example of a distributed automotive system with hard real-time requirements specified with the MechatronicUML method.

Virtuelle Inbetriebnahme eines Fertigungszentrums - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Tag des System Engineering)

Systematische Inbetriebnahme einer Prüfeinrichtung für Zugversuche - Holtkötter, Jens; Michael, Jan; Henke, Christian (Virtuelle Instrumente in der Praxis 2017)

Model-Based Design of Self-Correcting Forming Processes - Krüger, Martin; Borsig, Michael; Damerow, Ulf-Hendrik; Gräler, Manuel; Trächtler, Ansgar (Math for the Digital Factory)

A Holistic Approach for Virtual Commissioning of Intelligent Systems - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Systems Conference 2017)

Dynamische Prozessplanung im Smart Home auf Basis von Mutliagentensystemen - Michael, Jan; Hellweg, Alina; Henke, Christian; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Modellprädiktive Vorsteuerung für einen kinematisch redundanten hybridkinematischen Mechanismus im Industrieumfeld - Rüting, Arne Thorsten; Block, Eduard; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Sliding-Mode-Regler zur Kraft- und Positionsregelung eines Formgedächtnislegierung-Aktors - Pai, Arathi (Regelungstechnisches Kolloquium)

The MechatronicUML Design Method: Process and Language for Platform-Independent Modeling - Dziwok, Stefan; Pohlmann, Uwe; Piskachev, Goran; Schubert, David; Thiele, Sebastian; Gerking, Christopher
Several examples of mechatronic systems can be found nowadays in modern cars, production systems, and medical technology. Day by day, the number of innovative functionalities in such mechatronic systems is increasing. These functionalities are realized with complex software. Such software exhibits hard real-time, safety requirements. The adherence to these requirements must be thoroughly analyzed and verified. Moreover, to obtain a significant increment in the reliability, performance, and efficiency of such software, it needs to maintain the self-adaptation of its properties. In order to develop such systems with a high quality and within a short time, we need a systematic and consistent design method. For this purpose, the software engineering group at the University of Paderborn and the Fraunhofer IEM in Paderborn propose the MechatronicUML method. This method provides a comprehensive model-driven process support, that starts from requirements and reaches the executable software after passing through several design and analysis steps. This process improves the comprehension during development and makes complex systems manageable. MechatronicUML emphasizes mainly on: (1) modeling and (formal) verification of reconfigurable software architectures, (2) the coordination among system components in such architectures, and (3) the integration of discrete software events with the continuous behavior of control devices.

The MechatronicUML Requirements Engineering Method: Process and Language - Holtmann, Jörg; Fockel, Markus; Koch, Thorsten; Schmelter, David; Brenner, Christian; Bernijazov, Ruslan; Sander, Marcel
In this technical report, we present the MechatronicUML requirements engineering method. The method encompasses a process and a scenario-based modeling language for the documentation and analysis of requirements on the message-based interaction behavior of software-intensive systems. The modeling language uses a scenario notation based on Modal Sequence Diagrams (MSDs), which borrows concepts of UML Interactions as well as of Live Sequence Charts. Furthermore, we introduce the so-called Emergency Braking & Evasion System (EBEAS) as a running example, which is based on current and upcoming real-world driver assistance systems.

Das Erwachen der Macht – Automatische Softwareverteilung - Pohlmann, Uwe; Holtmann, Jörg; Meyer, Matthias (Tagungsband Embedded Software Engineering Kongress 2016)
Für die Ausführung der Software müssen die Softwarekomponenten auf ECUs verteilt werden. Dabei unterliegt die Verteilung sicherheitskritischen Constraints. Das Suchen der optimalen und gültigen Verteilung ist sehr komplex. Die Lösung kann effizient durch Verfahren des Operations Research ermittelt werden. Jedoch ist die manuelle Kodierung sehr aufwändig. Dieser Beitrag stellt eine modellgetriebene Methode und Werkzeugunterstützung vor, welche die Beschreibung von Constraints und Optimierungen vereinfacht sowie die formale Kodierung und Lösungssuche automatisiert. Dies erlaubt die effiziente Nutzung der Macht von formalen Modellen ohne Kenntnis der formalen mathematischen Verfahren. Die Vorteile der Methode werden anhand eines Beispiels aus der Automobilindustrie beschrieben.

Towards Feature-based Product Line Engineering of Technical Systems - Koch, Thorsten; Holtmann, Jörg; Schubert, David; Lindemann, Timo (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering (SysInt 2016))
The development of today’s technical products (e.g., in automation) is characterized by high customer expectations regarding the product individualization, which causes a wide range of product variants. Original equipment manufacturers (OEMs) can apply classical approaches from product line engineering, like feature modeling, to cope with the variability and the induced development complexity. Our tool support for feature models integrates a variety of feature model extensions like feature attributes and properties, logical constraints between features and feature properties, and the distinction between features and feature realizations. Furthermore, technical products have geometrical dimensions. The OEM specifies Computer Aided Design (CAD) models to consider these geometric dimensions and to virtually layout particular product variants. Geometric assembly constraints specify how parts of the product can be arranged in a CAD model. However, a potential product customer cannot configure an individual product variant and virtually layout this variant in the same software tool since the respective information stems from different sources. In order to cope with this problem, we present in this paper an extension of our tool support for feature models to specify geometric assembly constraints. Based on the proposed extension, we outline our research roadmap to consider these constraints in an online shop of an e-commerce system, in which a potential customer shall be able to configure a product variant and to virtually layout it according to the assembly constraints.

ASIL Tailoring on Functional Safety Requirements - Fockel, Markus (5th International Workshop on Next Generation of System Assurance Approaches for Safety-Critical Systems (SASSUR))
Cyber-physical systems like self-driving cars are highly complex and safety-critical. This results in a great number of safety requirements that have different levels of criticality. In automotive, the criticality is categorized in Automotive Safety Integrity Levels (ASIL). As a high ASIL causes high development effort, the goal is to develop most subsystems with lower ASIL requirements. To achieve this ASIL tailoring, subsystems need to be separated or redundantly implemented. These safety measures are usually integrated late in the development process and thus cause costly development iterations. In this paper, we present a systematic, tool-supported ASIL tailoring process for the requirements analysis phase. It is applied on formal safety requirements and automatically generated fault trees for a functional view of the system. The process supports early planning of safety efforts for mixed-criticality systems and avoids costly late development iterations.

Requirements Engineering - Zusatzaufgabe oder Kernkompetenz? - Holtmann, Jörg; Fockel, Markus; Koch, Thorsten; Schmelter, David (OBJEKTspektrum)
In verschiedenen Unternehmen wird mit Anforderungen unterschiedlich umgegangen. Je nach Größe, Branche und Unternehmenskultur ist das Thema Requirements Engineering (RE) mal weniger, mal mehr etabliert. In einigen Unternehmen wird es als lästige Zusatzaufgabe betrachtet, während andere Unternehmen ganze Abteilungen mit RE als Kernkompetenz betreiben. RE wird allerdings in jedem Projekt - bewusst oder unbewusst - durchgeführt! RE ist die Basis für den weiteren Entwicklungsprozess, die Validierung/Verifikation und die Plan- und Messbarkeit des Projekts. Darüber hinaus können Fehler, die auf Anforderungsebene gefunden werden, weniger aufwendig und somit günstiger behoben werden als in späteren Entwicklungsphasen. Am Fraunhofer IEM beraten wir Unternehmen und erforschen neue Methoden bezüglich der Entwicklung von intelligenten technischen Systemen. In diesem Artikel berichten wir über unsere Erfahrungen aus Projekten, in denen wir Unternehmen aus verschiedenen Branchen und mit unterschiedlichem RE-Reifegrad zwecks Leistungssteigerung des RE begleitet haben. Auf Basis dieser Projekterfahrungen zeigen wir Wege auf, wie der Stand des RE mittels eines Reifegradmodells im eigenen Unternehmen verbessert werden kann.

Integrated and iterative systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Journal of Software Evolution and Process)
The development of software-intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model-based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Towards Safe Execution of Reconfigurations in Cyber-Physical Systems - Schubert, David; Heinzemann, Christian; Gerking, Christopher (Proceedings of the 19th international ACM Sigsoft symposium on component-based software engineering)

PROFINET-Implementierung im Rahmen der Entwicklung eines intelligenten, selbstlernenden Teigkneters - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Oestersötebier, Felix; Wessels, Sebastian (Virtuelle Instrumente in der Praxis 2016)

A HRRN based scheduling for FMS and RMS with networked control and product-intelligence - Bertelsmeier, Fabian; Pollmann, Jan; Trächtler, Ansgar (Inproceedings of the IEEE IECON 2016)

Model Predictive Feedforward Compensation for Control of Multi Axes Hybrid Kinematics on PLC - Rüting, Arne Thorsten; Blumenthal, Lars Martin; Trächtler, Ansgar (Proceedings of IEEE IECON 2016)

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Graeler, Manuel; Henke, Christian; Hessel-von Molo, Mirko; Dellnitz, Michael; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Development and design of intelligent product carriers for ﬂexible networked control of distributed manufacturing processes - Bertelsmeier, Fabian; Schöne, Stefan; Trächtler, Ansgar (Inproceedings of the IEEE 24th Mediterranean Confernce on Control and Automation (MED))

Product Data and Sensor-based Intelligent Drive Control for Flexible Manufacturing and Intralogistic Processes - Geneiß, Volker; Hedayat, Christian; Bertelsmeier, Fabian; Henke, Christian; Vathauer, Karl-Ernst; Geßner, Thomas (Inproceedings of Smart Systems Integration 2016 International Conference and Exhibition on integration of materials, devices and systems)

Modellbildung und Simulation im Kontext des Systems Engineering - Michael, Jan; Holtkötter, Jens; Henke, Christian; Trächtler, Ansgar (ASIM-Treffen STS/GMMS 2016)

Implementing intelligent technical systems into smart homes by using model based systems engineering and multi-agent systems - Michael, Jan; Hillebrand, Michael; Wohlers, Benedict; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Renewable Energy and Power Quality Journal (RE&PQJ) 16)

Precision Control of SMA Actuators with a Real Time Model-Based Controller and Extended VSC - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IFAC-PapersOnLine)

A model extended temperature and strain controller modulated with PWM for precision position control of shape memory alloy actuators - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IEEE International Conference on Advanced Intelligent Mechatronics AIM)

Multidomänenmodell zur Optimierung der Hydraulik eines Raupenlaufwerks für Landmaschinen - Kruse, Daniel; Warkentin, Andreas P.; Krüger, Martin; Trächtler, Ansgar; Rackow, Sascha (Proc. 4. Internationales Commercial Vehicle Technology Symposium)

A Tool Chain for Model-Based Development of Heat Pump Dryers - Bockholt, Marcos; Katter, Michael; Pohl, Georg; Michael, Jan; Alpögger, Thomas (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Entwicklung einer modellbasierten In-the-Loop-Testumgebung für Waschautomaten. - Löffler, Alexander

Vom Systemmodell zu disziplinspezifischen Modellen und zurück - Schmitz, Joachim; Fockel, Markus (Tag des Systems Engineering 2015)
Zukünftige mechatronische Systeme entwickeln sich mehr und mehr zu intelligenten technischen Systemen, die durch eine zunehmende Verzahnung der mechanischen, elektrischen und informationsverarbeitenden Anteile gekennzeichnet sind. Um das Zusammenspiel der Disziplinen besser zu beherrschen, werden zunehmend Methoden und disziplinübergreifende Systemmodelle des Systems Engineering genutzt. Offene Probleme sind dabei noch die Nachverfolgbarkeit der Entwicklung (Traceability) und die Verwaltung zueinander konsistenter Versionen von disziplinübergreifenden und disziplinspezifischen Modellen. Dieser Beitrag adressiert diese Probleme durch die Verknüpfung der Spezifikationstechnik CONSENS für den Systementwurf mit dem Datenmanagementwerkzeug SYNECT. Der Beitrag stellt die Konzipierung und prototypische Werkzeugunterstützung für die Verknüpfung von Systemmodellen und disziplinspezifischen MATLAB/Simulink-Modellen vor.

Systementwurf unter Einbeziehung funktionaler Sicherheit bei automobilen Steuergeräten - Meyer, Jan; Fockel, Markus; Holtmann, Jörg (Tag des Systems Engineering 2015)
Automobile Steuergeräte realisieren mehr und mehr sicherheitskritische Funktionen. Nicht erst durch die Einführung der ISO 26262 werden an die Entwicklung sicherheitskritischer Funktionen besondere Anforderungen zum Beispiel in Form von Sicherheitsanalysen gestellt. In der Praxis hat sich herausgestellt, dass durch den bisherigen Systementwurf nicht alle notwendigen Daten für die Sicherheitsanalysen vorlagen. Von daher war eine Erweiterung des bisherigen Vorgehens erforderlich, sodass die benötigten Daten zu den erforderlichen Zeitpunkten vorliegen und die Sicherheitsanalysen ohne aufwendige Nacharbeiten erstellt werden können. Dieser Artikel beschreibt die durchgeführten Erweiterungen und die Erfahrungen, die in Serienprojekten eines automobilen Zulieferers gesammelt wurden.

ReqPat: Efficient Documentation of High-quality Requirements using Controlled Natural Language - Fockel, Markus; Holtmann, Jörg (Proc. of the 23rd International Requirements Engineering Conference 2015 (RE15))
The growing complexity of today's software intensive systems results in an increased size of requirements specifications, which are typically documented by means of natural language (NL). Large NL requirements specifications are prone to contain defects (e.g., contradictions), and the inherent ambiguity of NL impedes automatic techniques to support the requirements engineer. In order to cope with this problem, we conceived a requirements documentation approach implemented in the tool ReqPat. Using a controlled NL, it supports an efficient requirements documentation, an automatic requirements validation, and an automatic transition to models--while still keeping the requirements understandable for all stakeholders.

Model-Driven Allocation Engineering - Pohlmann, Uwe; Hüwe, Marcus (Conference: 30th IEEE/ACM International Conference on Automated Software Engineering (ASE 2015))
Cyber-physical systems (CPSs) provide sophisticated functionality and are controlled by networked electronic control units (ECUs). Nowadays, software engineers use component-based development approaches to develop their software. Moreover, software components have to be allocated to an ECU to be executed. Engineers have to cope with topology-, software-, and timing-dependencies and memory-, scheduling-, and routing-constraints. Currently, engineers use linear programs to specify allocation constraints and to derive a feasible allocation automatically. However, encoding the allocation problem as a linear program is a complex and error-prone task. This paper contributes a model-driven, OCL-based allocation engineering approach for reducing the engineering effort and to avoid failures. We validate our approach with an automotive case study modeled with MechatronicUML. Our validation shows that we can specify allocation constraints with less engineering effort and are able to derive feasible allocations automatically.

Integrated systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the 2015 International Conference on Software and System Process)
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and system models. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, for the discipline-specific development to start, these requirements need to be refined, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic transition from MBSE to model-based software requirements engineering, which we present in this paper. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach with an example of an automotive embedded system.

Generierung von AUTOSAR-Modellen aus UML-Spezifikationen - Meyer, Jan; Holtmann, Jörg; Koch, Thorsten; Meyer, Matthias (10. Paderborner Workshop Entwurf mechatronischer Systeme)
Die Komplexität moderner Fahrzeuge steigt aufgrund der zunehmenden Anzahl von Funktionen, die durch elektronische Systeme umgesetzt werden. Insbesondere nehmen die Abhängigkeiten zwischen den an der Entwicklung beteiligten Fachdisziplinen und der Softwareanteil massiv zu. Wir haben einen für die Automobilindustrie angepassten, zum Reifegradmodell Automotive SPICE konformen Prozess für die Entwicklung von Steuergeräten konzipiert, der ein fachdisziplinübergreifendes Systems Engineering und einen systematischen Übergang in die Softwareentwicklung unterstützt. Im Kontext dieses Entwicklungsprozess beschreiben wir in diesem Beitrag den Übergang vom UML-basierten Softwareentwurf zum in der Automobilindustrie etablierten AUTOSAR-Standard mit Hilfe einer automatischen Modelltransformation. So werden fehleranfällige und zeitaufwändige manuelle Tätigkeiten reduziert. Wir haben die Generierung von AUTOSAR-Modellen gemeinsam mit dem international tätigen Automobilzulieferer Hella KGaA Hueck & Co. in seriennahen Entwicklungsprojekten praktisch erprobt und Zeit- und Kostenersparnisse festgestellt.